Returns to Returning - Ira N. Gang; Catherine Y. Co; Myeong-Su Yun (Rutgers University, Department of Economics, 1999)
We examine the labor market performance of return migrants using the Hungarian Household Panel Survey. Two distinct selection issues are considered in the estimation of the earnings equation; we implement a natural method using MLE. The result that there is a 'premium' to work experience abroad for women is robust across the models we considered. For men, the return to working abroad is not generally significant.
Keywords: F22; J24; J61; 330; earnings; return migration; self-selection